Patient, carer and healthcare professional experiences of complex care quality in multidisciplinary primary healthcare centres: qualitative study with face-to-face, in-depth interviews and focus groups in five French multidisciplinary primary healthcare centres. Issue 12 (30th December 2021) - Derriennic, Jérémy; Barais, Marie; Le Goff, Delphine; Fernandez, Guillaume; Le Borne, Françoise; Le Reste, Jean-Yves
Abstract : Objectives: To explore care experiences in multidisciplinary primary healthcare centres from the patients, carers and healthcare professionals perspectives. Design: This qualitative study used face-to-face, in-depth interviews and focus groups. Patients with multimorbidity monitored by a General Practitioner (GP) and another professional from the health centre were recruited through purposive sampling and included with their carer. They were interviewed together while professionals were interviewed separately. Verbatims were coded with subsequent blind analysis, using an inductive approach, to find aspects and features. The constant comparative method highlighted data consistencies and variations. Participants: Twenty-six patients, 23 family carers and 57 healthcare professionals. Setting: Five multidisciplinary primary healthcare centres, in France, between March 2017 and December 2018. Results: This unique study grouped perspectives into nine core quality of primary care aspects: having accessible, available, and varied care; feeling welcome and enjoying comfortable, well-equipped, and clean premises; having quality medicotechnical care (medical knowledge and technical skills); having a reliable GP; receiving appropriate care from healthcare professionals other than the GP; maintaining an efficient relationship with healthcare professionals; benefiting from organised and coordinated care; being an informed, supported and involved patient; having an informed, supported and involved carer. New areas of interest include the multidisciplinary nature of the centres, appreciation of other professionals within the centre, medicotechnical dimensions of care and the carer's role in maintaining patient autonomy. Conclusions: This is the first study to interview patients and carers alongside healthcare professionals. This enhanced knowledge improves understanding of these aspects and can guide implementation of evaluation tools that truly reflect patient and carer needs and enable an efficient experience in terms of quality. To address deficiencies in existing questionnaires, the new perspectives found will be added to former aspects to create a comprehensive quality of primary care evaluation tool. Trial registration number: NCT02934711, Results.